Tveganja, koristi in upravljanje s tujerodnimi drevesnimi vrstami v alpskem prostoru - Simčič, Anica (Gozdarski vestnik, 2022)
The article presents the opinions and knowledge about non-native tree species (NNT) of the stakeholders who get in contact with NNT at their work in the forest, urban, and peri-urban areas in Slovenia. We obtained the opinions through an online survey in 2020; it took place in the framework of the ALPTREES project and was a part of the research in each of the five partner countries (Slovenia, Austria, Germany, Italy, and France) in the alpine space. We analyzed Slovenian stakeholders responses to obtain information on the stakeholders’ knowledge, understanding, and approach to NNT. Through an online survey, we obtained responses from 120 individuals. Analyzing the answers, we found that the majority of the respondents recognize NNT and invasive non-native tree species (INNT) in Slovenia. Generally, the respondents believe NNT bring risk into the alpine space. The respondents considered black locust (Robinia pseudoacacia), tree of heaven (Ailanthus altissima), princess tree (Paulownia tomentosa), Douglas fir (Pseudotsuga menziesii), northern red oak (Quercus rubra), and eastern white pine (Pinus strobus) to be the most widespread species. They place black locust, tree of heaven, princess tree, staghorn sumac (Rhus typhina), and boxelder (Acer negundo) among the most invasive ones. Just under half of the respondents expressed moderate concern about the impact of INNT, a quarter of the respondents was very concerned about NNT.
Keywords: alpski prostor; invazivne drevesne vrste; invazivne rastline; tujerodne drevesne vrste; tveganje; upravljanje